2021
DOI: 10.3390/cryst11070814
|View full text |Cite
|
Sign up to set email alerts
|

The Progress of Additive Engineering for CH3NH3PbI3 Photo-Active Layer in the Context of Perovskite Solar Cells

Abstract: Methylammonium lead triiodide (CH3NH3PbI3/MAPbI3) is the most intensively explored perovskite light-absorbing material for hybrid organic–inorganic perovskite photovoltaics due to its unique optoelectronic properties and advantages. This includes tunable bandgap, a higher absorption coefficient than conventional materials used in photovoltaics, ease of manufacturing due to solution processability, and low fabrication costs. In addition, the MAPbI3 absorber layer provides one of the highest open-circuit voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 187 publications
0
16
0
Order By: Relevance
“…The Tauc−Pankove relation shown in eq 14 can be used to calculate I(ω). 54 = E B E E ( ) g p (14) where E, B, and p are used for photon energy, transition probability, and DOS distribution, respectively. B is usually assumed to be constant over the entire optical frequency range.…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tauc−Pankove relation shown in eq 14 can be used to calculate I(ω). 54 = E B E E ( ) g p (14) where E, B, and p are used for photon energy, transition probability, and DOS distribution, respectively. B is usually assumed to be constant over the entire optical frequency range.…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
“…The renowned methylammonium lead triiodide perovskite (MAPbI 3 ) has been given a benchmark role in PSC technology and X-ray detection processes over the recent years due to the high charge/discharge dissociation characteristics, efficient light-absorbing behavior, low detection limit, interfacial charge-transfer properties, and rapid response speed. Recently, various two-dimensional (2D) materials such as graphene-based derivatives, Ti 3 C 2 T X , carbon nanotubes (CNTs), and transition-metal dichalcogenides (TMDs), including MoS 2 , MoSe 2 , and MoTe 2 , were intensively applied to modify the hole-transport layers (HTLs), electron-transport layers (ETLs), or active layers by a simple solution process, thereby reducing the edge/grain boundaries of perovskites or improving the interfacial relation with the active layer. Two-dimensional TMD materials are adopted as HTLs or active layers owing to their superior mechanical/electrical properties, high charge-transport mobility and conductivity, band gap tenability, and stability. Dasgupta et al reported that exfoliated MoS 2 nanosheets treated with ozone were employed as the HTL in PSCs to promote the hole transfer and effectively block the movement of electrons, resulting in the increase of 6.01% PCE compared to the PCE of 1.76% for the reference device without HTL.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47] Although ammonium/pyridinium halide derivatives and polymers have been studied widely as additives for controlling the morphology and repairing the crystal defects of perovskite lms, only a few papers have reported the synergistic effects of organic ammonium halides (or pyridinium halides) and polymers on the quality of perovskite thin lms. 17,48,49 Wang et al employed a polymeric salt, poly(1-vinyl-3-ethylacetate)imidazole tetrauoroborate (PEa), to modulate the crystallization and electronic properties of a perovskite. Their PEa contained multiple chemical anchoring sites capable of strong coordinative bonding to Pb ion defects at grain boundaries and at the interfaces of the perovskite lms, thereby effectively passivating electronic defects and enhancing the photo-, thermal-, and moisture-stability of the perovskite lms.…”
Section: Introductionmentioning
confidence: 99%
“…CH 3 NH 3 PbI 3 also referred to as MAPbI 3 (CH 3 NH 3 = methyl ammonium (MA))is the archetypical reference compound of the organolead halide perovskite materials family. The MAPbI 3 formulation is at the origin of the outstanding research on PSCs, initiated by Kojima et al in 2009 . The large absorption coefficient of the organolead halide perovskite photoabsorbers allows light to be absorbed by a thin layer, generally in the thickness range of 300–600 nm. , To further improve light harvesting, special attention has been paid over the recent years to enhance light–matter interactions and consequently the electric field intensity within the perovskite photoactive materials. …”
Section: Introductionmentioning
confidence: 99%
“…5 The large absorption coefficient of the organolead halide perovskite photoabsorbers allows light to be absorbed by a thin layer, generally in the thickness range of 300−600 nm. 4,6 To further improve light harvesting, special attention has been paid over the recent years to enhance light−matter interactions and consequently the electric field intensity within the perovskite photoactive materials. 7−9 Among different light management strategies, anti-reflective coatings, 10−12 textured surfaces, 13,14 plasmonic, 15−17 or light scattering layers 18 are used in photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%